2018
DOI: 10.1007/s00268-018-4708-5
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Reoperative Anti‐reflux Surgery: Low Perioperative Morbidity and High Symptom Resolution

Abstract: The robotic approach allows for minimal morbidity, short length of stay, and excellent functional outcomes in patients undergoing reoperative ARS when compared to patients undergoing primary ARS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…According to our findings, Elmously et al in 2018 reported a retrospective review of 200 patients (162 primary anti-reflux surgery and 38 reoperative surgery), concluding that the robotic approach leads to very low morbidity, short length of stay, and excellent functional outcomes in patients undergoing reoperative surgery when compared to patients undergoing primary anti-reflux surgery [ 13 ]. Furthermore, Elmously et al demonstrated that patients who underwent robotic redo surgery experienced complete or partial benefits from preoperative symptoms and more than 80% not require a daily PPI use [ 13 ].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…According to our findings, Elmously et al in 2018 reported a retrospective review of 200 patients (162 primary anti-reflux surgery and 38 reoperative surgery), concluding that the robotic approach leads to very low morbidity, short length of stay, and excellent functional outcomes in patients undergoing reoperative surgery when compared to patients undergoing primary anti-reflux surgery [ 13 ]. Furthermore, Elmously et al demonstrated that patients who underwent robotic redo surgery experienced complete or partial benefits from preoperative symptoms and more than 80% not require a daily PPI use [ 13 ].…”
Section: Discussionmentioning
confidence: 64%
“…Minimally invasive approach, which is the actual standard surgical approach for many complex surgical procedures [ 10 12 ], has also showed its benefit in the redo anti-reflux surgery. However, the conversion rate to open surgery is higher when compared to primary surgery, furthermore the robotic approach is described only in few cases [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…While robotic anti-reflux surgery has demonstrated postoperative outcomes comparable with the laparoscopic approach, some small studies have shown improved outcomes in cases of complex reoperative antireflux surgery with the robotic approach over the laparoscopic approach. Specifically, robotic-assisted reoperative anti-reflux operations have been associated with lower conversion rates, lower perforation and vagal nerve injury rates, lower readmission rates and decreased length of stay, as well as superior symptomatic relief and improved functional outcomes (22)(23)(24).…”
Section: Transitioning To a Robotic Thoracic Program: Why Do It?mentioning
confidence: 99%
“… 1 , 2 , 3 , 4 Although laparoscopy remains the most commonly used surgical approach, robotic surgery has proven to be a safe minimally invasive approach with potential surgical advantages and excellent functional outcomes. 5 …”
Section: Introductionmentioning
confidence: 99%